1970
DOI: 10.1021/ja00728a028
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Grignard reagents to vinylsilanes

Abstract: spectrum 45 (100) [HOCHCH3], 67 (10) [C5H7], 103 (11) (M -CIC2H4O], 138 (8) [M -C2H4O], 182 (parent ion, not seen, as is usual for secondary and tertiary alcohols). Anal. Caled for C7Hi2OC12:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1974
1974
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…We have also examined the efficacy of the ct-silylalkylmagnesium halide (VII), prepared by the addition of Grignard reagent ot an activated vinylsilane, in this olef¡nation. In agreement with the report by Buell,et al,19 we found that isopropylmagnesium chloride indeed added to dimethylvinylethoxysilane to generate the corresponding adduct VII (R = ¿-Pr). When benzaldehyde was added to a solution of adduct VII, a reaction occurred.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…We have also examined the efficacy of the ct-silylalkylmagnesium halide (VII), prepared by the addition of Grignard reagent ot an activated vinylsilane, in this olef¡nation. In agreement with the report by Buell,et al,19 we found that isopropylmagnesium chloride indeed added to dimethylvinylethoxysilane to generate the corresponding adduct VII (R = ¿-Pr). When benzaldehyde was added to a solution of adduct VII, a reaction occurred.…”
supporting
confidence: 93%
“…In agreement with the report by Buell, et a1., 19 we found that isopropylmagnesium chloride indeed added to dimethylvinylethoxysilane to generate the corresponding adduct VI1 (R = i-Pr). When benzaldehyde was added to a solution of adduct VII, a reaction occurred.…”
Section: VImentioning
confidence: 84%
See 1 more Smart Citation
“…It seems reasonable that the first step in the reaction of vinyldimethylchlorosilane with ZerZ-butyllithium leading to 4 is an addition reaction leading to the a-lithiochlorosilane, 5. While such additions are known,6 the only example of the addition of an organolithium reagent to a vinylsilane bearing substituents susceptible to nucleophilic displacement on silicon is contained in the original report of the reaction.63 In order to gain a better understanding of the relative rates of the coupling reaction of ZerZ-butyllithium with chlorosilanes and the addition to vinylsilanes, competition experiments in which equimolar mixtures of vinyltrimethylsilane and trimethylchlorosilane were treated with 1 equiv of ZerZ-butyllithium in hydrocarbon, ether, or tetrahydrofuran solvents were performed. In these experiments three products were isolated after hydrolytic workup: trans-1 -trimethylsilyl-3,3-dimethylbutene (6); 1,1 -bis(trimethylsilyl)-3,3-dimethylbutane (7); and 1,1,3-tris(trimethylsilyl)-5,5-dimethylhexane (8), all of which clearly arise from the initial addition of ZerZ-butyllithium to the vinylsilane. In none of the experiments was any tertbutyltrimethylsilane, the anticipated product from an initial coupling reaction, observed.…”
Section: Resultsmentioning
confidence: 99%
“…Deshalb sind diese als Reagentien in der organischen Synthese von großer Bedeutung 2. Die Methoden zur Herstellung von ( α ‐Silylalkyl)metallverbindungen basieren in der Regel entweder auf einer Deprotonierung,3 dem Halogen‐Metall‐Austausch mit Lithium oder Magnesium oder metallorganischen Verbindungen (BuLi oder RMgHal)4 oder der Addition einer metallorganischen Verbindung an Vinylsilane 5. Die letztgenannte Methode ist die effizienteste, da bei der Deprotonierung starke Basen wie t BuLi eingesetzt werden müssen, Alkylsilane ohne eine aktivierende Gruppe wie die Carbonylgruppe nicht effektiv deprotoniert werden können und die für die Halogen‐Metall‐Austauschreaktionen erforderlichen α ‐Halogenalkylsilane nicht einfach zugänglich sind.…”
Section: Methodsunclassified